1990
DOI: 10.1037/h0079063
|View full text |Cite
|
Sign up to set email alerts
|

Nurse and patient reactions to social displays of depression.

Abstract: The reactions of health-care staff toward depressed medical patients may be instrumental in reinforcing depressive behavior of patients. This analogue study examined the interpersonal responses of nursing staff and hospitalized patients with chronic medical conditions to a target who appeared either to have a chronic physical impairment or to be able-bodied, and who enacted either a depressed or nondepressed role. It was predicted that while nurses and patients would have negative reactions to the depressed ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…2 It has been observed that even nurses can become hostile to depressed patients. 3 Sometimes, we unthinkingly try to avoid or reduce our empathic response in these situations, either by escaping the situation, or through speech that attempts to force the sufferer to be happy.…”
Section: Empathic Distressmentioning
confidence: 99%
“…2 It has been observed that even nurses can become hostile to depressed patients. 3 Sometimes, we unthinkingly try to avoid or reduce our empathic response in these situations, either by escaping the situation, or through speech that attempts to force the sufferer to be happy.…”
Section: Empathic Distressmentioning
confidence: 99%